2012
DOI: 10.22201/ib.20078706e.2012.1.1133
|View full text |Cite
|
Sign up to set email alerts
|

Helmintos gastrointestinales en aves acuáticas de la subcuenca alta del río Lerma, México

Abstract: Resumen. Se realizó un inventario y se calcularon los parámetros de infección de los helmintos gastrointestinales de 36 ejemplares de aves acuáticas pertenecientes a las familias Anatidae, Rallidae y Threskiornithidae, procedentes de la subcuenca alta del río Lerma, Estado de México, identificándose 20 especies: 9 tremátodos, 8 céstodos, 2 nemátodos y 1 acantocéfalo. De las 8 especies de céstodos, 6 son registros nuevos para el país y Pseudocorynosoma constrictum se registra por primera vez en Anas crecca, Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
2
3
0
4
Order By: Relevance
“…The heterogeneity of our samplings, along geographical, age-related, and avian gender, could be determinants for the observed differences (see Bush, 1990 ). Likewise, the richness of helminth species in some of these studies [21 in Padilla-Aguilar et al (2018) , 25 in Farias and Canaris (1986) , and 20 in Martínez-Haro et al, 2012 )] is similar to our findings (23). These richness values are in accordance with the Fedynich and Pence (1994) statement, who pointed out that the taxonomic composition and infections of individual hosts are determined by the seasonality of the samples, as well as by the vagility of the birds, which promote the exchange of helminths along their migratory route.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The heterogeneity of our samplings, along geographical, age-related, and avian gender, could be determinants for the observed differences (see Bush, 1990 ). Likewise, the richness of helminth species in some of these studies [21 in Padilla-Aguilar et al (2018) , 25 in Farias and Canaris (1986) , and 20 in Martínez-Haro et al, 2012 )] is similar to our findings (23). These richness values are in accordance with the Fedynich and Pence (1994) statement, who pointed out that the taxonomic composition and infections of individual hosts are determined by the seasonality of the samples, as well as by the vagility of the birds, which promote the exchange of helminths along their migratory route.…”
Section: Discussionsupporting
confidence: 91%
“…Taxonomic composition of helminth fauna of Mexican waterfowl does not seem to follow a structured pattern; in our study, nematodes and trematodes were the best represented groups of helminths among anatids, with eleven and six species, respectively. Similar findings were reported by Padilla-Aguilar et al (2018) (eight nematodes and seven trematodes) in the Altangatepec wetlands, in Central Mexico; on the contrary, Martinez-Haro et al (2012) registered nine trematodes and eight cestodes in the Lerma marshes, also in Central Mexico. On the other hand, studies conducted in Northern Mexico revealed a higher presence of platyhelminths.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, the knowledge of nematodes from anatids in South America is very scarce. Most investigations have been carried out in Chile, Mexico (González et al, 2005; Mercado Reyes et al, 2010; Martínez Haro et al, 2012) and Brazil (Vicente et al, 1996; Vianna Mohr, 2001), while information about Argentina is still lacking (da Silveira et al, 2006; Agüero & Diaz, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…and Sobolevicanthus gracilis Zeder, 1803 have been recorded in C. atratus, C. buccinator, C. cygnus, and C. olor from Asia, Europe, and North America (MCDONALD, 1969;BLUS et al, 1989;ZUCHOWSKA, 1997). In the neotropics there are few findings, with a report in waterfowl from Mexico: Sobolevicanthus krabella Hughes, 1940 and S. gracilis;(FARIAS & CANARIS, 1986;MARTÍNEZ-HARO et al, 2012). For the black-necked swan, Pfeiffer (1960) isolated R. bulbocirrosus from captive birds in Austria; nevertheless, the author specified that the birds died soon after their arrival from Argentina.…”
Section: Discussionmentioning
confidence: 99%